2022
DOI: 10.3390/ijerph191610369
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Relationship of Resistance Training on Metabolic Phenotypes, Body Composition and Lipid Profile in Menopausal Women

Abstract: The relationship between volume training of resistance training (RT), body composition and cardiometabolic profile in menopausal women is poorly understand. This study aimed to evaluate the dose–response relationship of RT on lipid profile, body composition and metabolic phenotypes in menopausal women. A total of 31 women were categorized according to different volume of RT. Body composition was evaluated by DEXA and the cardiometabolic risk by metabolic phenotypes and lipid profile. There was a higher frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In a study examining groups of postmenopausal women with similar weight loss, only the group that exercised experienced a favorable shift in body composition with a reduction in the android to gynoid fat mass ratio [ 114 ]. Research has also shown a dose–response effect of exercise on fat loss and metabolic parameters [ 115 , 116 ]. Earnest et al examined how different “doses” of exercise affected metabolism and found, remarkably, that significant improvement seen in waist circumference, fasting glucose, and systolic blood pressure were dose-dependent, once again highlighting the therapeutic effect of exercise, especially among aging women [ 117 ].…”
Section: Exercise Improves Metabolic Health Following the Menopausementioning
confidence: 99%
“…In a study examining groups of postmenopausal women with similar weight loss, only the group that exercised experienced a favorable shift in body composition with a reduction in the android to gynoid fat mass ratio [ 114 ]. Research has also shown a dose–response effect of exercise on fat loss and metabolic parameters [ 115 , 116 ]. Earnest et al examined how different “doses” of exercise affected metabolism and found, remarkably, that significant improvement seen in waist circumference, fasting glucose, and systolic blood pressure were dose-dependent, once again highlighting the therapeutic effect of exercise, especially among aging women [ 117 ].…”
Section: Exercise Improves Metabolic Health Following the Menopausementioning
confidence: 99%